Mathematical model of the relationship between pH holding time and erosive esophagitis healing rates - Howden, Colin W.; Scarpignato, Carmelo; Leifke, Eckhard; Mulford, Darcy J.; Lahu, Gezim; Facius, Axel; Yuan, Yuhong; Hunt, Richard (CPT: pharmacometrics and systems pharmacology, 2025)
Effective suppression of gastric acid secretion promotes healing of erosive esophagitis. Treatment guidelines recommend proton pump inhibitors (PPIs) and histamine H2–receptor antagonists (H2RAs). Emerging evidence also supports potassium‐competitive acid blockers (P‐CABs). The aim was to construct a mathematical model to examine the relationship between pH holding time ratios (HTRs) and erosive esophagitis healing rates with H2RAs, PPIs and P‐CABs. By literature search, we identified studies of H2RAs, PPIs or P‐CABs that reported mean pH >4 HTRs at steady state (days 5–8) and erosive esophagitis healing rates after 4 and/or 8 weeks. We aggregated treatments by drug class and developed a non‐linear, mixed‐effects model to explore the relationship between pH >4 HTRs and healing rates. The pH dataset included 82 studies (4297 participants; 201 dosage arms); healing rate data came from 103 studies (43,417 patients; 196 treatment arms). P‐CABs achieved the longest periods with intragastric pH >4, and the highest healing rates after 4 and 8 weeks. The predicted probabilities of achieving ≥90% healing rates at 8 weeks were 74.1% for P‐CABs, 17.3% for PPIs and 0% for H2RAs. P‐CABs provide the longest duration with intragastric pH >4 and, accordingly, the highest healing rates of erosive esophagitis.